تخصصاتِ نبویﷺ ؛ شرح صحیح مسلم ازغلام رسول سعیدی کی روشنی میں - Ali, Dr Muhammad Waris; Khalil, Fatima (AL-IDRAK JOURNAL, 2022)
Almighty Allah has given high ranks to His last last Prophet Hazrat Muhammad ﷺ. He has the characteristics that are found only in his personality. This research is based on descriptive method and has been conducted to discuss the qualities of the last prophet in the light of Sharh Sahih Muslim by Ghulam Rasool Saedi. The examples from this book have been selected to analyse and discuss the said qualities. It can be concluded that Allama Ghulam rasool saedi has described the personal charateristics of the Prophet Hazrat Muhammad ﷺ in his unique way. His method to describe the seerat of the prophet shows that the dignity and respect of the last prophet is base of every aspect of Islamic teachings.